Pengelolaan Informasi Publik di Tinjau dari Perspektif Good Governance di Kabupaten Bengkalisy - Astuti, Junia; As’ari, Hasim; Adianto, Adianto; Anjani, Nurul (Peneliti.net, 2024)
This research is motivated by Public Information Openness (KIP) in Bengkalis Regency which has obligations and challenges in meeting the public information needs of its entire community. The problem of implementing KIP democratically in Bengkalis Regency stems from the mental readiness of regional officials or public bodies as well as the readiness of the community to truly maximize the function of supervision and participation in order to realize good governance. The aim of this research is to analyze and explain the management of public information from the perspective of good governance and the obstacles faced as well as the efforts made in managing public information at the Bengkalis Regency Communication and Information Technology Department. This research uses a qualitative research method with an explanatory phenomenological approach. . The primary data was obtained directly through interviews from informants, namely the head of the Bengkalis district communications and information services department, secretaries, public information management and services (PPID) staff, heads of communications and information resources, heads of electronic-based management, journalists, non-governmental organizations (LSM) and society. The results of this research show that the management of public information within the Bengkalis Regency Government which is handed over to the Bengkalis Regency Diskominfotik Public Agency as the Main PPID, viewed from a good governance perspective, consists of 4 (four) principles, namely accountability, transparency, participation and professionalism. Globally, the four principles of good governance have been implemented by diskominfotik, although not yet optimally because there are several obstacles from both internal and external parties. However, efforts are still being made by diskominfotik to prevent obstacles from emerging which aim to improve the government system so that the Bengkalis can be realized with dignity, progress and prosperity (Bermasa).